ANALISIS SISTEM INFORMASI MANAJEMEN KEPEGAWAIAN DALAM MENINGKATKAN EFEKTIVITAS PEMBINAAN DI LAPAS KELAS III SUKAMARA - M.Yanuar; Milka Milka (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2025)
Entering the era of the industrial revolution 4.0. The ease of obtaining information or internet access is increasingly felt by most people, including in the Class III Sukamara Penitentiary (Lapas). This convenience is felt to greatly facilitate employees in terms of administration, especially for Sukamara Prison officers, who are greatly assisted in accessing the Personnel Management Information System (Simpeg) application. The personnel management information system to improve the quality of personnel administration data management which currently has 52 ASN on duty at Sukamara III Prison. The personnel management information system or SIMPEG at the Class III Sukamara Penitentiary is one form of e-government implementation in transparent and objective personnel services, in addition to presenting personnel information, it is also specifically designed to improve services in the field of personnel administration such as rank, transfer or mutation and dismissal of State Civil Apparatus from and in office. The research approach used in this study is qualitative with a literature study research method. The literature research period is calculated from October 1, 2024 to review and search for relevant reference sources. In order for communication patterns and a high sense of responsibility to be formed, socialization efforts must be carried out routinely so that employees (ASN) can truly understand the goals, roles, functions and a series of benefits from using the digital-based personnel system application. This will have a positive impact on the development of the Sukamara Class III prison, which is innovative, progressive towards innovations that lead to good information technology in order to realize a prison with optimal digitalization services